Confirmation of Skywalker Hoolock Gibbon (Hoolock tianxing) in Myanmar Extends Known Geographic Range of an Endangered Primate - Pyae Phyo Aung; Ngwe Lwin; Tin Htun Aung; Thura Soe Min Htike; Carolyn Thompson; Christian Roos; Sa Myo Zaw; L. Zawng Lum; Win Naing Oo; Zung Sau; Samuel T. Turvey; Wai Zinn Thein; et al. (International Journal of Primatology, 2024)
Characterizing genetically distinct populations of primates is important for protecting biodiversity and effectively allocating conservation resources. Skywalker gibbons ( Hoolock tianxing ) were first described in 2017, with the only confirmed population consisting of 150 individuals in Mt. Gaoligong, Yunnan Province, China. Based on river geography, the distribution of the skywalker gibbon has been hypothesized to extend into Myanmar between the N’Mai Kha and Ayeyarwaddy Rivers to the west, and the Salween River (named the Thanlwin River in Myanmar and Nujiang River in China) to the east. We conducted acoustic point-count sampling surveys, collected noninvasive samples for molecular mitochondrial cytochrome b gene identification, and took photographs for morphological identification at six sites in Kachin State and three sites in Shan State to determine the presence of skywalker gibbons in predicted suitable forest areas in Myanmar. We also conducted 50 semistructured interviews with members of communities surrounding gibbon range forests to understand potential threats. In Kachin State, we audio-recorded 23 gibbon groups with group densities ranging between 0.57 and 3.6 group/km 2 . In Shan State, we audio-recorded 21 gibbon groups with group densities ranging between 0.134 and 1.0 group/km 2 . Based on genetic data obtained from skin and saliva samples, the gibbons were identified as skywalker gibbons (99.54–100% identity). Although these findings increase the species’ known population size and confirmed distribution, skywalker gibbons in Myanmar are threatened by local habitat loss, degradation, and fragmentation. Most of the skywalker gibbon population in Myanmar exists outside protected areas. Therefore, the IUCN Red List status of the skywalker gibbon should remain as Endangered.

Observed characteristics of flow, water mass, and turbulent mixing in the Preparis Channel - Ruijie Ye; Feng Zhou; Xiao Ma; Dingyong Zeng; Feilong Lin; Hongliang Li; Chenggang Liu; Soe Moe Lwin; Hlaing Swe Win; Soe Pyae Aung (Acta Oceanologica Sinica, 2023)